2021
DOI: 10.3389/fpsyt.2021.584287
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Prenatal Depression: A Cross-Sectional Study in Rural Pakistan

Abstract: Objective: To determine the prevalence and association of prenatal depression with socioeconomic, demographic and personal factors among pregnant women living in Kallar Syedan, Rawalpindi, Pakistan.Methods: Five hundred women in the second and third trimester of pregnancy, living in Kallar Syedan, a rural area of district Rawalpindi Pakistan, were included in the study. Depression was assessed using “Patient health questionnaire” (PHQ9) in Urdu, with a cut-off score of 10. Multi-dimensional scale of perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 63 publications
3
14
1
Order By: Relevance
“… 18 Likewise, a study from Pakistan revealed that women who had multiple pregnancies were twice (OR: 2.3, 95% CI: 1.33 to 3.91) more likely to suffer from antenatal depression. 46 A similar finding was revealed by a study from India where the women who had multiple pregnancies had twice (AOR: 2.36, 95% CI: 1.19 to 4.66) the odds of depression as compared with women who were pregnant for the first time. 47 Women in multigravida not only have more exposure to the potential complications associated with pregnancy and childbirth, but they are also more stressed to fulfil the demands of the newborn child while bearing responsibility as a mother to their other children.…”
Section: Discussionsupporting
confidence: 75%
“… 18 Likewise, a study from Pakistan revealed that women who had multiple pregnancies were twice (OR: 2.3, 95% CI: 1.33 to 3.91) more likely to suffer from antenatal depression. 46 A similar finding was revealed by a study from India where the women who had multiple pregnancies had twice (AOR: 2.36, 95% CI: 1.19 to 4.66) the odds of depression as compared with women who were pregnant for the first time. 47 Women in multigravida not only have more exposure to the potential complications associated with pregnancy and childbirth, but they are also more stressed to fulfil the demands of the newborn child while bearing responsibility as a mother to their other children.…”
Section: Discussionsupporting
confidence: 75%
“…Our participants, in particular, are primarily city dwellers. Women with twin pregnancies having antenatal examinations in rural hospitals may be more prone to anxiety and depression [ 68 ]. So, this study cannot represent the entire population of women pregnant with twins.…”
Section: Discussionmentioning
confidence: 99%
“…Despite teenage pregnancy and coming from low-income backgrounds 15 pregnant adolescents delivered healthy babies because of possessing positive factors such as self-efficacy, motivation to achieve career goals, and having a strong support system, which the authors referred to as a resiliency framework [67]. In Pakistan, however, the majority of women belong to patriarchal family systems, lack participation in domestic decision making, lack autonomy, and with illiteracy this leads to indecisiveness, poor self-confidence, and prenatal depression, culminating in low resilience [68].…”
Section: Discussionmentioning
confidence: 99%